Ocean acidification in Canada: the current state of knowledge and pathways for action - Kristina M. Barclay; Helen J. Gurney-Smith; Mohamed Ahmed; James R. Christian; Frédéric Cyr; Patrick J. Duke; Brent G. T. Else; Iria Gimenez; Martine Lizotte; M. Catherine Reader; Myron Roth; Krysten Rutherford; et al. (Frontiers in Marine Science, 2026)
Ocean acidification (OA) generally receives far less consideration than other climate stressors and related hazards, such as global warming and extreme weather events. Canada is uniquely vulnerable to OA given its extensive coastal oceans, the oceanographic processes in its three basins, accelerated warming and sea-ice melt, and extensive coastal communities and maritime economic sectors. Canada’s coastline is also home to extensive and diverse First Nations peoples with distinct histories, rights, title, laws, governance and whose traditions and cultures are extrinsically linked to the sea. However, there are currently very limited pathways to support OA action, mitigation, and/or adaptation in Canada, particularly at the policy level. Here, we present a first synthesis of the current state of OA knowledge across Canada's Pacific, Arctic, and Atlantic regions, including monitoring, modelling, biological responses, socioeconomic and policy perspectives, and examples of existing OA actions and efforts at local and provincial levels. We also suggest a step-wise pathway for actions to enhance the coordinated filling of OA knowledge gaps and integration of OA knowledge into decision-making frameworks. The goals of these recommendations are to improve our ability to respond to OA in Canada, and minimize risks to coastal marine environments and ecosystems, vulnerable sectors, and communities.

Formative influences: How capital shapes rural students’ college-going intentions - Sarah Rutt Williams; Anne M. Hornak; Skylar R. Duke; Frimpomaa Ampaw (Journal of Rural Studies, 2025)

Correction to: Synthesizing a preliminary framework of the core constructs of climate change acceptance - Jessica R. Duke; Emily A. Holt (Climatic Change, 2025)

Synthesizing a preliminary framework of the core constructs of climate change acceptance - Jessica R. Duke; Emily A. Holt (Climatic Change, 2025)

A Quantitative Classification of the Geography of Non‐Native Flora in the United States - Bethany A. Bradley; Annette E. Evans; Helen R. Sofaer; Montserrat Vilà; David T. Barnett; Evelyn M. Beaury; Dana M. Blumenthal; Jeffrey D. Corbin; Jeffrey S. Dukes; Regan Early; Inés Ibáñez; Ian S. Pearse; et al. (Global Ecology and Biogeography, 2025)
Aim Non‐native plants have the potential to harm ecosystems. Harm is classically related to their distribution and abundance, but this geographical information is often unknown. Here, we assess geographical commonness as a potential indicator of invasive status for non‐native flora in the United States. Geographical commonness could inform invasion risk assessments across species and ecoregions. Location Conterminous United States. Time Period Through 2022. Major Taxa Studied Plants. Methods We compiled and standardised occurrence and abundance data from 14 spatial datasets and used this information to categorise non‐native species as uncommon or common based on three dimensions of commonness: area of occupancy, habitat breadth and local abundance. To assess consistency in existing categorizations, we compared commonness to invasive status in the United States. We identified species with higher‐than‐expected abundance relative to their occupancy, habitat breadth or residence time. We calculated non‐native plant richness within United States ecoregions and estimated unreported species based on rarefaction/extrapolation curves. Results This comprehensive database identified 1874 non‐native plant species recorded in 4,844,963 locations. Of these, 1221 species were locally abundant (> 10% cover) in 797,759 unique locations. One thousand one hundred one non‐native species (59%) achieved at least one dimension of commonness, including 565 species that achieved all three. Species with longer residence times tended to meet more dimensions of commonness. We identified 132 species with higher‐than‐expected abundance. Ecoregions in the central United States have the largest estimated numbers of unreported, abundant non‐native plants. Main Conclusions A high proportion of non‐native species have become common in the United States. However, existing categorizations of invasive species are not always consistent with species' abundance and distribution, even after considering residence time. Considering geographical commonness and higher‐than‐expected abundance revealed in this new dataset could support more consistent and proactive identification of invasive plants and lead to more efficient management practices.

Out of sight, into the spotlight: Beyond the current state of science on per- and poly-fluoroalkyl substances in groundwater - Odera R. Umeh; Eziafakaego M. Ibo; Chima I. Eke; Duke U. Ophori (Journal of Environmental Management, 2025)

Molecular basis of hyper-thermostability in the thermophilic archaeal aldolase MfnB - Rosie M. A. Maddock; Carl O. Marsh; Samuel T. Johns; Lynden D. Rooms; Phillip W. Duke; Marc W. van der Kamp; James E. M. Stach; Paul R. Race (Extremophiles, 2024)
Methanogenic archaea are chemolithotrophic prokaryotes that can reduce carbon dioxide with hydrogen gas to form methane. These microorganisms make a significant contribution to the global carbon cycle, with methanogenic archaea from anoxic environments estimated to contribute > 500 million tons of global methane annually. Archaeal methanogenesis is dependent on the methanofurans; aminomethylfuran containing coenzymes that act as the primary C 1 acceptor molecule during carbon dioxide fixation. Although the biosynthetic pathway to the methanofurans has been elucidated, structural adaptations which confer thermotolerance to Mfn enzymes from extremophilic archaea are yet to be investigated. Here we focus on the methanofuran biosynthetic enzyme MfnB, which catalyses the condensation of two molecules of glyceralde-3-phosphate to form 4‑(hydroxymethyl)-2-furancarboxaldehyde-phosphate. In this study, MfnB enzymes from the hyperthermophile Methanocaldococcus jannaschii and the mesophile Methanococcus maripaludis have been recombinantly overexpressed and purified to homogeneity. Thermal unfolding studies, together with steady-state kinetic assays, demonstrate thermoadaptation in the M. jannaschii enzyme. Molecular dynamics simulations have been used to provide a structural explanation for the observed properties. These reveal a greater number of side chain interactions in the M. jannaschii enzyme, which may confer protection from heating effects by enforcing spatial residue constraints.

Groundwater systems under siege: The silent invasion of microplastics and cock-tails worldwide - Odera R. Umeh; Duke U. Ophori; Eziafakaego M. Ibo; Chima I. Eke; Toritseju P. Oyen (Environmental Pollution, 2024)

Monitoring cotton water status with microtensiometers - Clay G. Christenson; Mohammad R. Gohardoust; Sebastian Calleja; Kelly R. Thorp; Markus Tuller; Duke Pauli (Irrigation Science, 2024)
Stem water potential (Ψ stem ) is a key indicator for assessing plant water status, which is crucial in understanding plant health and productivity. However, existing measurement methods for Ψ stem , characterized by destructiveness and intermittency, limit its applicability. Microtensiometers, an emerging plant-based sensor, offer continuous monitoring capabilities and have shown success in certain vine and tree species. In this study, we investigate the efficacy of microtensiometers ability to monitor the Ψ stem of cotton ( Gossypium hirsutum L.) under three distinct irrigation treatments in Maricopa, Arizona, an extremely hot, arid environment. We analyze the diurnal dynamics of Ψ stem across the irrigation regimes and compare these measurements with midday leaf water potentials (Ψ leaf ) obtained using a dewpoint potentiometer. Our results demonstrate that the microtensiometer-derived Ψ stem closely follows known diurnal patterns of Ψ leaf , tracking with vapor pressure deficit (VPD) and responding to variations in irrigation levels and soil moisture content. Time cross-correlation analysis reveals an 80-minute lag in Ψ stem response to changing VPD under non-water limiting conditions, which shortens under water-limiting conditions. Additionally, we establish a robust linear relationship ( R 2 adj = 0.82) between Ψ stem and Ψ leaf , with this relationship strengthening as water availability decreases. Notably, we observe mean gradients of 1.2 and 0.06 MPa between soil vs. stem and stem vs. leaf water potentials, respectively. Moreover, Ψ stem data proves to be more sensitive in distinguishing between irrigation treatments earlier in the growing season compared to Ψ leaf , leaf temperature and leaf gas exchange parameters. These findings highlight the utility of microtensiometers as valuable tools for monitoring water status in smaller-stemmed row crops such as cotton.

Co-processing of end-of-life wind turbine blades in portland cement production - Anton K. Schindler; Steve R. Duke; W. Braxton Galloway (Waste Management, 2024)

Investigating the role of incident ion flux in solar wind space weathering of carbon-rich asteroidal regolith via H+ and He+ irradiation of the Murchison meteorite - D.L. Laczniak; M.S. Thompson; R. Christoffersen; C.A. Dukes; R.V. Morris; L.P. Keller (Icarus, 2024)

Macroscale analyses suggest invasive plant impacts depend more on the composition of invading plants than on environmental context - Evelyn M. Beaury; Helen R. Sofaer; Regan Early; Ian S. Pearse; Dana M. Blumenthal; Jeffrey D. Corbin; Jeffrey Diez; Jeffrey S. Dukes; David T. Barnett; Inés Ibáñez; Laís Petri; Montserrat Vilà; et al. (Global Ecology and Biogeography, 2023)
Aim Native biodiversity is threatened by the spread of non‐native invasive species. Many studies demonstrate that invasions reduce local biodiversity but we lack an understanding of how impacts vary across environments at the macroscale. Using ~11,500 vegetation surveys from ecosystems across the United States, we quantified how the relationship between non‐native plant cover and native plant diversity varied across different compositions of invading plants (measured by non‐native plant richness and evenness) and environmental contexts (measured by productivity and human activity). Location Continental United States. Time Period Surveys from 1990s‐present. Major Taxa Studied Terrestrial plant communities. Methods We fit mixed effects models to understand how native plant richness, diversity and evenness varied with non‐native cover. We tested how this relationship varied when non‐native cover interacted with non‐native plant richness and evenness, and with productivity and human activity. Results Across the United States, communities with greater cover of non‐native plants had lower native plant richness and diversity but higher evenness, suggesting rare native plants can be lost while dominant plants decline in abundance. The relationship between non‐native cover and native community diversity varied with non‐native plant richness and evenness but was not associated with productivity and human activity. Negative associations were strongest in areas with low non‐native richness and evenness, characterizing plant communities that were invaded by a dominant non‐native plant. Main Conclusions Non‐native plant cover provides a first approximation of invasion impacts on native community diversity, but the magnitude of impact depended on non‐native plant richness and evenness. Relationships between non‐native cover and native diversity were consistent in strength across continental scale gradients of productivity and human activity. Therefore, at the macroscale, invasive plant impacts on native plant communities likely depend more on the characteristics of the invading plants, that is the presence of a dominant invader, than on the environmental context.

Defining the toxicological profile of 4-hydroxyphenylpyruvate dioxygenase-directed herbicides to Aedes aegypti and Amblyomma americanum - Sarah E. McComic; Stephen O. Duke; Edwin R. Burgess; Daniel R. Swale (Pesticide Biochemistry and Physiology, 2023)

Current and legacy effects of precipitation treatments on growth and nutrition in contrasting crops - Erin D. Jackson; Christian Casolaro; Ryan S. Nebeker; Eric R. Scott; Jeffrey S. Dukes; Timothy S. Griffin; Colin M. Orians (Agriculture, Ecosystems & Environment, 2023)

On the origins of backscattered solar wind energetic neutral hydrogen from the Moon and Mercury - F. Leblanc; R. Deborde; D. Tramontina; E. Bringa; J.Y. Chaufray; S. Aizawa; R. Modolo; L. Morrissey; A. Woodson; S. Verkercke; C. Dukes (Planetary and Space Science, 2023)

Molecular targets of insecticides and herbicides – Are there useful overlaps? - Stephen O. Duke; Zhiqiang Pan; Amar G. Chittiboyina; Daniel R. Swale; Thomas C. Sparks (Pesticide Biochemistry and Physiology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A novel survey of raptor collections in Europe and their potential to provide samples for pan-European contaminant monitoring - Gloria Ramello; Guy Duke; Rene W. R. J. Dekker; Steven van der Mije; Paola Movalli (Environmental Science and Pollution Research, 2022)
This paper provides a novel survey of current collections of frozen raptor carcasses and tissue samples in natural history museums (NHMs), environmental specimen banks (ESBs) and other research collections (ORCs e.g. at universities and research institutes) across Europe and assesses the extent to which collections might support pan-European raptor biomonitoring through the provision of samples for contaminant analyses. The paper is based on questionnaire responses received in late 2018 and early 2019 from 116 institutions. Issues covered include the number of raptor carcasses and diversity of raptor species arriving annually at collections, the number of carcasses stored in freezers, the extent to which collections retain frozen tissue samples, what records are kept of carcasses and tissue samples, constraints to expanding collections of frozen carcasses and tissues and the extent to which collections currently engage in ecotoxicological research and monitoring. Our findings show that collections in Europe receive well over 5000 raptor carcasses per annum, and that NHMs are the key recipients of raptor carcasses for most countries. Collections in Europe probably hold well over 10,000 raptor carcasses in their freezers, offering a substantial resource of frozen raptor carcasses and tissues from recent years. Moreover, these carcasses include good specimen numbers for species that have been prioritized for pan-European contaminant monitoring. Collections are becoming digitized aiding access to samples. However, freezer capacity is a key constraint to retention of carcasses, and contaminant biomonitoring is novel for most NHMs. Our findings on the repository and availability of frozen raptor carcasses and tissues held by collections in Europe can enable greater use of these specimens for pan-European contaminant monitoring in support of better chemicals management. We highlight opportunities to further optimize raptor collections for pan-European contaminant monitoring.

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Agricultural impacts of climate change in Indiana and potential adaptations - Laura C. Bowling; Keith A. Cherkauer; Charlotte I. Lee; Janna L. Beckerman; Sylvie Brouder; Jonathan R. Buzan; Otto C. Doering; Jeffrey S. Dukes; Paul D. Ebner; Jane R. Frankenberger; Benjamin M. Gramig; Eileen J. Kladivko; et al. (Climatic Change, 2020)

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Current In Vitro Assays for Prediction of T Cell Mediated Immunogenicity of Biotherapeutics and Manufacturing Impurities - Brian R. Duke; Shibani Mitra-Kaushik (Journal of Pharmaceutical Innovation, 2020)

Perspectives on in situ Sensors for Ocean Acidification Research - Akash R. Sastri; James R. Christian; Eric P. Achterberg; Dariia Atamanchuk; Justin J. H. Buck; Philip Bresnahan; Patrick J. Duke; Wiley Evans; Stephen F. Gonski; Bruce Johnson; S. Kim Juniper; Steve Mihaly; et al. (Frontiers in Marine Science, 2019)

How do climate change experiments alter plot‐scale climate? - A. K. Ettinger; I. Chuine; B. I. Cook; J. S. Dukes; A. M. Ellison; M. R. Johnston; A. M. Panetta; C. R. Rollinson; Y. Vitasse; E. M. Wolkovich (Ecology Letters, 2019)
To understand and forecast biological responses to climate change, scientists frequently use field experiments that alter temperature and precipitation. Climate manipulations can manifest in complex ways, however, challenging interpretations of biological responses. We reviewed publications to compile a database of daily plot‐scale climate data from 15 active‐warming experiments. We find that the common practices of analysing treatments as mean or categorical changes (e.g. warmed vs. unwarmed) masks important variation in treatment effects over space and time. Our synthesis showed that measured mean warming, in plots with the same target warming within a study, differed by up to 1.6 C (63% of target), on average, across six studies with blocked designs. Variation was high across sites and designs: for example, plots differed by 1.1 C (47% of target) on average, for infrared studies with feedback control ( n = 3) vs. by 2.2 C (80% of target) on average for infrared with constant wattage designs ( n = 2). Warming treatments produce non‐temperature effects as well, such as soil drying. The combination of these direct and indirect effects is complex and can have important biological consequences. With a case study of plant phenology across five experiments in our database, we show how accounting for drier soils with warming tripled the estimated sensitivity of budburst to temperature. We provide recommendations for future analyses, experimental design, and data sharing to improve our mechanistic understanding from climate change experiments, and thus their utility to accurately forecast species’ responses.

Warming and Elevated CO2 Interact to Alter Seasonality and Reduce Variability of Soil Water in a Semiarid Grassland - Dana M. Blumenthal; Kevin E. Mueller; Julie A. Kray; Daniel R. LeCain; Elise Pendall; Sara Duke; T. Jane Zelikova; Feike A. Dijkstra; David G. Williams; Jack A. Morgan (Ecosystems, 2018)

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Public health implications of social media use during natural disasters, environmental disasters, and other environmental concerns - Kathryn C. Finch; Kassandra R. Snook; Carmen H. Duke; King-Wa Fu; Zion Tsz Ho Tse; Atin Adhikari; Isaac Chun-Hai Fung (Natural Hazards, 2016)

Global patterns and substrate‐based mechanisms of the terrestrial nitrogen cycle - Shuli Niu; Aimée T. Classen; Jeffrey S. Dukes; Paul Kardol; Lingli Liu; Yiqi Luo; Lindsey Rustad; Jian Sun; Jianwu Tang; Pamela H. Templer; R. Quinn Thomas; Dashuan Tian; et al. (Ecology Letters, 2016)
Nitrogen (N) deposition is impacting the services that ecosystems provide to humanity. However, the mechanisms determining impacts on the N cycle are not fully understood. To explore the mechanistic underpinnings of N impacts on N cycle processes, we reviewed and synthesised recent progress in ecosystem N research through empirical studies, conceptual analysis and model simulations. Experimental and observational studies have revealed that the stimulation of plant N uptake and soil retention generally diminishes as N loading increases, while dissolved and gaseous losses of N occur at low N availability but increase exponentially and become the dominant fate of N at high loading rates. The original N saturation hypothesis emphasises sequential N saturation from plant uptake to soil retention before N losses occur. However, biogeochemical models that simulate simultaneous competition for soil N substrates by multiple processes match the observed patterns of N losses better than models based on sequential competition. To enable better prediction of terrestrial N cycle responses to N loading, we recommend that future research identifies the response functions of different N processes to substrate availability using manipulative experiments, and incorporates the measured N saturation response functions into conceptual, theoretical and quantitative analyses.

Tracking pan-continental trends in environmental contamination using sentinel raptors—what types of samples should we use? - S. Espín; A. J. García-Fernández; D. Herzke; R. F. Shore; B. van Hattum; E. Martínez-López; M. Coeurdassier; I. Eulaers; C. Fritsch; P. Gómez-Ramírez; V. L. B. Jaspers; O. Krone; et al. (Ecotoxicology, 2016)

Nicotine reinforcement in never-smokers - Angela N. Duke; Matthew W. Johnson; Chad J. Reissig; Roland R. Griffiths (Psychopharmacology, 2015)

Discovery and structure activity relationships of 2-pyrazolines derived from chalcones from a pest management perspective - Bedia Koçyiğit-Kaymakçıoğlu; Nagihan Beyhan; Nurhayat Tabanca; Abbas Ali; David E. Wedge; Stephen O. Duke; Ulrich R. Bernier; Ikhlas A. Khan (Medicinal Chemistry Research, 2015)

Diversity and bioprospection of fungal community present in oligotrophic soil of continental Antarctica - Valéria M. Godinho; Vívian N. Gonçalves; Iara F. Santiago; Hebert M. Figueredo; Gislaine A. Vitoreli; Carlos E. G. R. Schaefer; Emerson C. Barbosa; Jaquelline G. Oliveira; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; Silvane M. F. Murta; et al. (Extremophiles, 2015)

Involvement of facultative apomixis in inheritance of EPSPS gene amplification in glyphosate-resistant Amaranthus palmeri - Daniela N. Ribeiro; Zhiqiang Pan; Stephen O. Duke; Vijay K. Nandula; Brian S. Baldwin; David R. Shaw; Franck E. Dayan (Planta, 2014)

Clinical correlation and molecular evaluation confirm that the MLH1 p.Arg182Gly (c.544A>G) mutation is pathogenic and causes Lynch syndrome - Michael P. Farrell; David J. Hughes; Ian R. Berry; David J. Gallagher; Emily A. Glogowski; Stewart J. Payne; Michael J. Kennedy; Róisín M. Clarke; Susan A. White; Cian B. Muldoon; Fiona Macdonald; Pauline Rehal; et al. (Familial Cancer, 2012)

Simple additive effects are rare: a quantitative review of plant biomass and soil process responses to combined manipulations of CO 2 and temperature - Wouter I. J. Dieleman; Sara Vicca; Feike A. Dijkstra; Frank Hagedorn; Mark J. Hovenden; Klaus S. Larsen; Jack A. Morgan; Astrid Volder; Claus Beier; Jeffrey S. Dukes; John King; Sebastian Leuzinger; et al. (Global Change Biology, 2012)
In recent years, increased awareness of the potential interactions between rising atmospheric CO 2 concentrations ([ CO 2 ]) and temperature has illustrated the importance of multifactorial ecosystem manipulation experiments for validating Earth System models. To address the urgent need for increased understanding of responses in multifactorial experiments, this article synthesizes how ecosystem productivity and soil processes respond to combined warming and [ CO 2 ] manipulation, and compares it with those obtained in single factor [ CO 2 ] and temperature manipulation experiments. Across all combined elevated [ CO 2 ] and warming experiments, biomass production and soil respiration were typically enhanced. Responses to the combined treatment were more similar to those in the [ CO 2 ]‐only treatment than to those in the warming‐only treatment. In contrast to warming‐only experiments, both the combined and the [ CO 2 ]‐only treatments elicited larger stimulation of fine root biomass than of aboveground biomass, consistently stimulated soil respiration, and decreased foliar nitrogen (N) concentration. Nonetheless, mineral N availability declined less in the combined treatment than in the [ CO 2 ]‐only treatment, possibly due to the warming‐induced acceleration of decomposition, implying that progressive nitrogen limitation ( PNL ) may not occur as commonly as anticipated from single factor [ CO 2 ] treatment studies. Responses of total plant biomass, especially of aboveground biomass, revealed antagonistic interactions between elevated [ CO 2 ] and warming, i.e. the response to the combined treatment was usually less‐than‐additive. This implies that productivity projections might be overestimated when models are parameterized based on single factor responses. Our results highlight the need for more (and especially more long‐term) multifactor manipulation experiments. Because single factor CO 2 responses often dominated over warming responses in the combined treatments, our results also suggest that projected responses to future global warming in Earth System models should not be parameterized using single factor warming experiments.

The effect of experimental warming and precipitation change on proteolytic enzyme activity: positive feedbacks to nitrogen availability are not universal - Edward R. Brzostek; John M. Blair; Jeffrey S. Dukes; Serita D. Frey; Sarah E. Hobbie; Jerry M. Melillo; Robert J. Mitchell; Elise Pendall; Peter B. Reich; Gaius R. Shaver; Artur Stefanski; Mark G. Tjoelker; et al. (Global Change Biology, 2012)
Nitrogen regulates the E arth's climate system by constraining the terrestrial sink for atmospheric CO 2 . Proteolytic enzymes are a principal driver of the within‐system cycle of soil nitrogen, yet there is little to no understanding of their response to climate change. Here, we use a single methodology to investigate potential proteolytic enzyme activity in soils from 16 global change experiments. We show that regardless of geographical location or experimental manipulation (i.e., temperature, precipitation, or both), all sites plotted along a single line relating the response ratio of potential proteolytic activity to soil moisture deficit, the difference between precipitation and evapotranspiration. In particular, warming and reductions in precipitation stimulated potential proteolytic activity in mesic sites – temperate and boreal forests, arctic tundra – whereas these manipulations suppressed potential activity in dry grasslands. This study provides a foundation for a simple representation of the impacts of climate change on a central component of the nitrogen cycle.

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Detecting substrate engagement: responses of tarsal campaniform sensilla in cockroaches - Sasha N. Zill; Bridget R. Keller; Sumaiya Chaudhry; Elizabeth R. Duke; David Neff; Roger Quinn; Clay Flannigan (Journal of Comparative Physiology A, 2010)

Influence of dietary carbohydrate intake on the free testosterone: cortisol ratio responses to short-term intensive exercise training - Amy R. Lane; Joseph W. Duke; Anthony C. Hackney (European Journal of Applied Physiology, 2010)

Current Practices and Future Opportunities for Policy on Climate Change and Invasive Species - CHRISTOPHER R. PYKE; ROXANNE THOMAS; READ D. PORTER; JESSICA J. HELLMANN; JEFFREY S. DUKES; DAVID M. LODGE; GABRIELA CHAVARRIA (Conservation Biology, 2008)
Climate change and invasive species are often treated as important, but independent, issues. Nevertheless, they have strong connections: changes in climate and societal responses to climate change may exacerbate the impacts of invasive species, whereas invasive species may affect the magnitude, rate, and impact of climate change. We argue that the design and implementation of climate‐change policy in the United States should specifically consider the implications for invasive species; conversely, invasive‐species policy should address consequences for climate change. The development of such policies should be based on (1) characterization of interactions between invasive species and climate change, (2) identification of areas where climate‐change policies could negatively affect invasive‐species management, and (3) identification of areas where policies could benefit from synergies between climate change and invasive‐species management.

Tuning posture to body load: decreases in load produce discrete sensory signals in the legs of freely standing cockroaches - Bridget R. Keller; Elizabeth R. Duke; Ayman S. Amer; Sasha N. Zill (Journal of Comparative Physiology A, 2007)

Molecular Phylogenetic Relationships Among Crested-tailed Mice (Genus Habromys) - Duke S. Rogers; Christopher C. Funk; Jacqueline R. Miller; Mark D. Engstrom (Journal of Mammalian Evolution, 2007)

Natural and anthropogenic changes to mangrove distributions in the Pioneer River Estuary (QLD, Australia) - Stacy D. Jupiter; Donald C. Potts; Stuart R. Phinn; Norman C. Duke (Wetlands Ecology and Management, 2007)

The search for a marsupial XIC reveals a break with vertebrate synteny - Lance S. Davidow; Matthew Breen; Shannon E. Duke; Paul B. Samollow; John R. McCarrey; Jeannie T. Lee (Chromosome Research, 2007)

Use of tricyclic antidepressants in older patients with painful neuropathies - Ariel Berger; Ellen M. Dukes; John Edelsberg; Brett R. Stacey; Gerry Oster (European Journal of Clinical Pharmacology, 2006)

C-Lock (Patent Pending): A System for Estimating and Certifying Carbon Emission Reduction Credits for the Sequestration of Soil Carbon on Agricultural Land - Patrick R. Zimmerman; Maribeth Price; Changhui Peng; William J. Capehart; Karen Updegraff; Patrick Kozak; Lee Vierling; Elaine Baker; Fred Kopp; Genet Duke; Chandan Das (Mitigation and Adaptation Strategies for Global Change, 2005)

Odorant receptor gene expression changes during the parr–smolt transformation in Atlantic salmon - J. P. DUKES; R. DEAVILLE; M. W. BRUFORD; A. F. YOUNGSON; W. C. JORDAN (Molecular Ecology, 2004)
The ability of salmon to home accurately to their natal stream to spawn has long intrigued biologists and has important consequences for the maintenance of population structure in these species. It is known that olfaction is crucial to homing, and that the transition from the freshwater to the marine environment (the parr–smolt transformation; PST) is a period of increased olfactory sensitivity and learning, resulting in a permanent memory of natal site odours that is retained, at least in part, in peripheral sensory neurones. These odours are then used as cues by sexually maturing fish on their homeward migration. We used quantitative polymerase chain reaction techniques to demonstrate transient increases in expression of odorant receptor transcripts (of up to fifty‐fold over pre‐PST levels) coincident with PST. Both olfactory ( SORB ) and vomeronasal receptors ( SVRA and SVRC ) are involved, which suggests that the fish learn both environmental odours and semiochemicals (pheromones). Receptor expression varies between families and changes over time indicating both genetic differences in odour stimuli and multiple periods of olfactory sensitivity. We suggest that changes in OR gene expression may have a role in homing behaviour and thus the maintenance of population structure in Atlantic salmon.

Atlantic salmon change the expression of odorant receptor genes to learn the smell of home - W. C. Jordan; J. P. Dukes; R. Deaville; M. W. Bruford; A. F. Youngson (Journal of Fish Biology, 2003)
The ability of salmon to home to their natal stream to spawn has long intrigued biologists. It is known that olfaction is crucial to accurate homing, and that the transition between freshwater and marine environments (the parr‐smolt transformation; PST) is a period of increased olfactory sensitivity and learning, resulting in a permanent memory of natal site odours that is retained in peripheral sensory neurons. These odours are then used as cues by sexually maturing fish on their homeward migration. We have used molecular techniques to demonstrate transient increases in expression of odourant receptor transcripts coincident with PST. Both olfactory and vomeronasal receptors are involved, which suggests that the fish learn both environmental odours and semiochemicals (pheromones). Receptor expression varies between families and changes over time indicating both genetic differences in odour stimuli and multiple periods of olfactory sensitivity. We hypothesise that changes in gene expression may have a role in maintaining population structure in Atlantic salmon.

Interdisciplinary Irrigated Precision Farming Research - D. F. Heermann; J. Hoeting; S. E. Thompson; H. R. Duke; D. G. Westfall; G. W. Buchleiter; P. Westra; F. B. Peairs; K. Fleming (Precision Agriculture, 2002)

DDT Toxicity and Critical Body Residue in the Amphipod Leptocheirus plumulosus in Exposures to Spiked Sediment - G. R. Lotufo, J. D. Farrar, B. M. Duke (Archives of Environmental Contamination and Toxicology, 2001)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Kappa opioid-mediated behavioral sensitization in the preweanling rat: relationship to Fos immunoreactivity - R. L. Collins; A. R. Zavala; V. Y. Ingersoll; M. A. Duke; C. A. Crawford; S. A. McDougall (Psychopharmacology, 1998)

Selective Growth Inhibition of the Musty-Odor Producing Cyanobacterium Oscillatoria cf. chalybea by Natural Compounds - K. K. Schrader; M. Q. de Regt; P. R. Tidwell; C. S. Tucker; S. O. Duke (Bulletin of Environmental Contamination and Toxicology, 1998)

The "prismane" protein resolved: X-ray structure at 1.7 Å and multiple spectroscopy of two novel 4Fe clusters - Alexander F. Arendsen; Jonathan Hadden; Graeme Card; Alan S. McAlpine; Susan Bailey; Vjacheslav Zaitsev; Elizabeth H. M. Duke; P. F. Lindley; Monika Kröckel; Alfred X. Trautwein; Martinus C. Feiters; John M. Charnock; et al. (JBIC Journal of Biological Inorganic Chemistry, 1998)

Effects of long-term hypergravity on muscle, heart and lung structure of mice - Markus Frey; Ruth von Känel-Christen; Vilma Stalder-Navarro; Pauline Jackie Duke; Ewald R. Weibel; Hans Hoppeler (Journal of Comparative Physiology B, 1997)

Effect of nitrogen supply on expression of some genes controlling storage proteins and carbohydrate synthesis in cultured maize kernels - Douglas C. Doehlert; Edwin R. Duke; Leslie J. Smith (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)

Human keratinocytes maintain reversible anti-apoptotic defenses in vivo and in vitro - D. A. Norris; M. H. Middleton; K. Whang; M. Schleicher; T. McGovern; S. D. Bennion; K. David-Bajar; D. Davis; R. C. Duke (Apoptosis, 1997)

Nutritional control of xanthine dehydrogenase. II. Effects on xanthine dehydrogenase and aldehyde oxidase of culturing wild-type and mutant Drosophila on different levels of molybdenum - E. J. Duke; D. R. Rushing; E. Glassman (Biochemical Genetics, 1975)